Case of rare association of peripheral neuropathy with mixed connective tissue disorder. Issue 4 (22nd April 2021) - Sethi, Prativa Priyadarshani; Sudan, Aditya; Kumari, Suman; Pathania, Monika
Abstract : Chronic inflammatory demyelinating polyneuropathy (CIDP) is probably the best-recognised progressive immune-mediated peripheral neuropathy. It presents with symmetrical, motor predominant peripheral neuropathy that produces both distal and proximal weakness. Here we report a case of a 38-year-old man who presented with chronic additive large and small joint inflammatory polyarthritis, associated with morning stiffness, anasarca associated with frothy urine and progressive episodic, relapsing and remitting, sensorimotor lower motor neuron type quadriparesis without any bladder and bowel involvement. He was diagnosed as a case of CIDP, and the aetiology was found out to be mixed connective tissue disorder, which is a rare association with CIDP. The patient responded dramatically to glucocorticoid.